Modulation of atrial fibrillation susceptibility by gp91phox-containing NADPH oxidases - Mighiu, A (2018)
Atrial fibrillation (AF) is the most frequently encountered cardiac rhythm disorder in humans, with affected individuals facing an increased risk of stroke and mortality. Published findings implicate oxidative stress in triggering the new onset of AF and in promoting the atrial electrical and structural changes that drive disease progression. NOX2-containing NADPH oxidases are a significant source of superoxide production in atrial tissues. Previous work showed that a NOX2-mediated increase in superoxide accompanies AF in patients and animal models of tachypacing-induced AF, and further reported a strong independent association between atrial NOX2 activity and post-operative AF in patients undergoing cardiac surgery. However, a direct causal role for NOX2 in AF has not been investigated. This thesis aimed to test the hypothesis that superoxide released specifically from NOX2 directly contributes to the development of AF. To investigate the role of NOX2 in AF, mice with cardiac-specific overexpression of the human NOX2 gene (NOX2-Tg) were characterized. Atrial homogenates from these mice were found to show approximately 3-fold higher expression of NOX2 protein compared with wild-type controls, which was associated with a significant increase in NADPH-stimulated superoxide production. AF susceptibility assessed in vivo by transesophageal atrial burst stimulation was significantly higher in NOX2-Tg mice compared with wild-type, in the absence of significant alterations in cardiac function. However, dietary administration of atorvastatin (30 mg/kg daily for two weeks) did not eliminate AF susceptibility in NOX2-Tg mice, despite preventing the increase in NADPH-stimulated superoxide production in the left and right atria of these animals. Instead, atorvastatin significantly reduced the duration of pacing-induced AF, an effect which was found to be independent of genotype, and thus independent of NOX2 inhibition. Mechanistic studies do not support a role for NOX2 in promoting electrical or structural remodelling, as high-resolution optical mapping of di-4-ANEPPS-stained atrial tissue preparations revealed no significant differences in action potential duration or conduction velocity between wild-type and NOX2-Tg mice. Instead, NOX2 overexpression was associated with impaired atrial Ca2+ handling. In left atrial myocytes of NOX2-Tg mice, the RyR2 Ca2+ leak-SR load ratio was lower when compared with wild-type, despite an increase in SR Ca2+ load. In the right atria, the leak-load ratio was similar between NOX2-Tg and wild-type myocytes, but the proportion of myocytes with ‘leaky’ RyR2 channels was greater among NOX2-Tg mice. RyR2 phosphorylation at Ser-2814 and Ser-2808 was not significantly different between WT and NOX2-Tg atrial homogenates, indicating that the changes in diastolic leak are not caused by differences in CaMKII or PKA activity.